The Effect of Futsal Extracurricular Activities on The Development of Attitude and Teamwork among Students - Sarah Amelia Fitriani; Carsiwan; Sufyar Mudjianto (Journal of Physical Education Health and Sport, 2026)
In today’s gadget-dominated world, fostering positive attitudes and teamwork among students is of utmost importance, given the negative effects of prolonged gadget use and the resulting addiction. Character education in schools plays a vital role in fostering a generation of citizens with positive values. One school program that plays a significant role is the futsal extracurricular activity conducted outside the classroom. The purpose of this study is to determine whether the futsal extracurricular activity can effectively develop attitudes and teamwork among students at Junior High School 3 Lembang . The method used is a quantitative approach with a causal-comparative research design. The sample in this study was selected using purposive sampling, comprising 40 students: a futsal extracurricular group (n = 20) and a non-futsal extracurricular control group (n = 20). The study utilized a questionnaire instrument with a Likert scale that had been validated for both validity and reliability. The data analysis employed descriptive statistics and inferential statistics. The results of the descriptive statistics showed a significant difference in the High category. The experimental group (students participating in the futsal extracurricular activity) scored 100% on both the attitude and teamwork variables, far higher than the control group (students not participating in the futsal extracurricular activity), which scored only 55% (attitude) and 5% (teamwork). The results of the inferential statistics for both variables yielded a Sig. (2-tailed) value < 0.001. The Effect Size test (Cohen’s d) for the attitude variable yielded a value of 1.229, and for teamwork, 1.257. Conclusion: This study shows that futsal extracurricular activities are highly effective in developing students’ attitudes and teamwork skills as a solution to the widespread use of gadgets.